Simple soldering : a beginner's guide to jewelry making - Richbourg, Kate Ferrant (Loveland, CO : Interweave, 2012)
"Metalworking is generally regarded as a skill that takes years of dedication, requires a large studio space, and costs a lot of money. Fortunately, Simple Soldering proves that does not need to be the case. This handy how-to guide is complete in its exploration of the craft of creating soldered metal jewelry, including tools, techniques, and 20 beautiful projects that beginners and enthusiasts can make at home. Author and teacher Kate Richbourg demystifies basic soldering for any home crafter, showing how to create sophisticated, polished, and professional- looking jewelry pieces through simple soldering techniques. First, she instructs how to set up a jewelry workspace that fits the confines of your budget and living space. Detailed step-by-step instructions walk you through the basic tools and materials you need, plus how to use them. A sample chapter gives a host of introductory exercises that teach solid skills, allowing you to test these techniques on a small scale. Finally, you'll discover 20 finished projects that include earrings, pendants, rings, bracelets, and clasps that may also include bead or wire embellishment. Kate also demonstrates how to combine and layer techniques to gorgeous effect. She also examines common mistakes, shows how to correct or adapt them, and gives advice on when it's time to start over. Most of all, having taught thousands of classes on soldering, Kate has a "you can do it!" attitude that shines through to help even the most reluctant jewelry maker fire up the torch with ease. Paired with an instructional DVD, Kate's expert teaching skills will help projects come alive, right in your own studio. With Simple Soldering, the art of metal working one-of-a-kind jewelry is now at your fingertips. "--
The basics -- Setting up a work space -- The tools -- The materials -- Creating your sampler -- The projects.
Includes bibliographical references and index.
Keywords: Jewelry making; Solder and soldering